2021
DOI: 10.1002/ecs2.3350
|View full text |Cite
|
Sign up to set email alerts
|

High‐density camera trap grid reveals lack of consistency in detection and capture rates across space and time

Abstract: Counts of independent photo events from camera traps are commonly used to make inference about species occupancy, the density of unmarked populations, and the relative abundance of species across time and space. These applications rest on the untested assumption that data collected from individual cameras are representative of the landscape location in which they are placed, and that nearby cameras would record similar data when any additional micro‐site differences are accounted for. We established a high‐den… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 63 publications
2
20
0
Order By: Relevance
“…Our study confirms an increasing body of work showing that microsite characteristics, whether measurable with covariates or not, have a large influence on detection probabilities of species on CTs (Kolowski and Forrester 2017, Evans et al 2019, Kolowski et al 2021. Several species had different detection probabilities at microsites that were defined by different features (forest roads, wildlife trails, or cliff sides), likely due to differences among species in their microsite selection.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…Our study confirms an increasing body of work showing that microsite characteristics, whether measurable with covariates or not, have a large influence on detection probabilities of species on CTs (Kolowski and Forrester 2017, Evans et al 2019, Kolowski et al 2021. Several species had different detection probabilities at microsites that were defined by different features (forest roads, wildlife trails, or cliff sides), likely due to differences among species in their microsite selection.…”
Section: Discussionsupporting
confidence: 83%
“…We also found contrasting results across species of the effects of visibility in front of the CT on detection probabilities. These are also likely related to differences in habitat selection and movement strategy among the species (Kolowski et al 2021) rather than differences in PIR-sensor sensitivity (Rowcliffe et al 2011, Hofmeester et al 2017. Movement of lynx, red foxes, mountain hares, and red squirrels, as predators and small prey, are more channeled toward sites with a short line of sight (many obstructions) compared to roe deer, which could explain the contrasting patterns we found between these species.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…Most practitioners presume their results are representative of large, vaguely-defined areas, but some studies suggest otherwise. For example Kays et al [19] found little spatial autocorrelation in detection rates past 25 m for five Central American mammal species and Kolowski et al [20] found no spatial autocorrelation at any scale, suggesting that cameras may represent small areas. While it might be safe to extend the inference of species presence directly in front of a camera trap to larger scales (e.g.…”
Section: Introductionmentioning
confidence: 99%